Remarks on the destape and spectacularization of the violence of State terrorism in Argentina during the last democratic transition (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
During the last democratic transition in Argentina, after the progressive lifting of censorship, sexuality invaded the media along with the first truly massive narratives in the country of the crimes committed by the dictatorship. This paper is a first approach to this singular articulation between sexuality and politics that took place in the post-dictatorship framework. First, I make a critical review of the concept of “destape” and its analytical implications, and then explore different aspects of the ways in which the violence of State terrorism was narrated in the media during the first months of 1984, in order to reflect on the ethical-political dimension of the testimony and the logic of spectacle in relation to the politics of memory.
Keywords: politics of memory, violence, sexuality, media